Perbandingan Bunyi Dua Ragam Bahasa; 'Amiyah dan Fusha dalam Lagu Karya Nancy Ajram - Difla Nur Imtiyas; Kholisin Kholisin (Institut Agama Islam Negeri Metro, 2022)
When viewed from its variety, Arabic can be divided into two forms: standard variety Arabic (fushah) and non-standard variety Arabic (amiyah). In Arabic, the sounds of vowels and consonants can change according to the speakers, such as the Egyptian speakers 'amiyah, who could not pronounce Arabic fusha perfectly, and vice versa. This led to the appearance of sound changes between the two varieties of language. This study aims to analyze the forms of sound changes 'amiyah Egyptian dialect (BADM) and Arabic fushah (BAF). In this research, researchers will analyze using Crowley's theory of sound change. The data in this study is in the form of lyrics of 5 songs by Nancy Ajram, Lebanese nationality, but his work dialect Egypt. The results showed that BADM and BAF have differences in pronunciation that cause the appearance of sound changes. The types of sound changes that occur following Crowley's theory are (1) lenition and fortition, (2) tough loss, (3) good addition, (4) metathesis, (5) assimilation, and (6) tone changes.